Characteristics of Sodium Lithium Titanate Synthesized at Different Solid-State Reaction Temperature for Lithium-Ion Battery Anode - Yahya, Ilham Nur Dimas; Sofyan, Nofrijon; Khaerudini, Deni Shidqi; Timuda, Gerald Ensang; Priyono, Slamet (Journal of Materials Exploration and Findings, 2023)
The effect of sintering temperature on the characteristics of sodium lithium titanate (NaLiTi3O7/NaLTO) synthesized at different solid-state reaction temperature and its performance as lithium-ion battery anode has been investigated. The precursors for the synthesis consisted of LiOH.H2O, TiO2, and NaHCO3. The synthesis was performed via solid-state reaction method. The precursors were mixed and sintered at variation temperatures of 900oC, 1000oC, and 1100oC for 2 hours under atmosphere condition. The final product was characterized using X-ray diffraction (XRD) and particle size analyzer (PSA). The XRD analysis showed the main phase of NaLTO with some impurities. PSA analysis showed that the sintering temperature has a significant effect on changes in particle size where the sample at a temperature of 1100oC has the largest particle size of 74.62 µm. The battery was fabricated by firstly mixing NaLTO powder with polyvinylidene fluoride (PVDF) and acetylene black (AB) in a ratio of 85:10:5 wt.% and the mix was then deposited onto copper foil to form NaLTO a sheet. The NaLTO sheet was cut into circular discs with a diameter of 14 mm and were arranged in a sequence of separator, metallic lithium, and electrolyte to form a coin cell in a glove box. Characterization using cyclic voltammetry (CV) and charge-discharge (CD) showed that the NaLTO sintered at 1000oC provided good electrochemical performance with the largest diffusion coefficient of 3.948 x 10-10 m2/s, Coulombic efficiency reached 100%, and a high specific capacity of 65.83 mAh/g.